MAM 2006 : an international conference to celebrate the 150th anniversary of the birth of A.A. Markov : June 12-14 - Langville, Amy N.; Stewart, William J., 1946- (Boson Books, 2006)
The Markov Anniversary Meeting, June 12-14, 2006 was the fifth in a series of conferences devoted to the Numerical Solution of Markov Chains (NSMC). The prior four NSMC conferences were held in 1990, 1995, 1999, and 2003. The first two conferences were held in Raleigh, North Carolina, the third moved overseas to Zarazoga, Spain, and the fourth was held in Urbana-Champaign, Illinois. This fifth and most recent Markov meeting occurred sooner than the usual 4-5 year schedule in order to celebrate two very important events: the 150th anniversary of Andrei A. Markov's birth and the 100th anniversar.